1995
DOI: 10.1042/bj3081009
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of d-myo-inositol 1,4,5-trisphosphate 3-kinase from bovine iris sphincter smooth muscle: effects of protein phosphorylation in vitro and in intact muscle

Abstract: Stimulation of bovine iris sphincter muscle with carbachol (10 microM) increased accumulation of Ins(1,4,5)P3 (InsP3) and Ins(1,3,4,5)P4 (InsP4) by 86 and 32% respectively. Addition of isoproterenol (5 microM) to muscle pretreated with carbachol reduced the 3H-radioactivity in InsP3 by 30% and increased that of InsP4 by 41%. InsP3 3-kinase was predominantly localized in the soluble fraction (110,000 g supernatant) of the iris sphincter. The enzyme was purified from this fraction by sequential chromatography on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Also, these studies do not address the possibility of a membrane-associated activity in the tissues or cell lines examined. When membrane fractions have been analysed, IP $ 3-kinase activity has been detected in turkey erythrocytes [54] and bovine iris sphincter smooth muscle [55]. Taken together, these data present strong evidence in favour of an IP $ 3-kinase activity being present in intracellular membranes.…”
Section: Discussionmentioning
confidence: 68%
“…Also, these studies do not address the possibility of a membrane-associated activity in the tissues or cell lines examined. When membrane fractions have been analysed, IP $ 3-kinase activity has been detected in turkey erythrocytes [54] and bovine iris sphincter smooth muscle [55]. Taken together, these data present strong evidence in favour of an IP $ 3-kinase activity being present in intracellular membranes.…”
Section: Discussionmentioning
confidence: 68%
“…Regulation of IP3K Activity by Phosphorylation-In addition to stimulation by calcium/calmodulin, phosphorylation is another well documented mode of regulating IP3K activity (17)(18)(19)(20)(21)(22)(23)(24)(25)(26). To compare the effect of phosphorylation on the activity of the two isoforms of IP3K, the purified, recombinant proteins were phosphorylated in vitro with pure PKA and PKC and examined for the stoichiometry of phosphorylation and changes in activity.…”
Section: Comparison Of the Regulatory Properties Of The Inositol 14mentioning
confidence: 99%
“…The IP3K is also a substrate for the cyclic AMP-dependent protein kinase, the calcium/calmodulin-dependent protein kinase II, and protein kinase C in vitro. When the IP3K purified from rat brain or bovine smooth muscle is phosphorylated by the cyclic AMP-dependent protein kinase in vitro, its activity is increased about 2-fold (17,18) while phosphorylation of the protein by protein kinase C reduced activity to about 25% of the basal activity (17)(18)(19). Phosphorylation of IP3K from brain with the calcium/calmodulindependent protein kinase II increases its V max about 9-fold and decreases the K m for calmodulin from 52 to 2 nM (20).…”
mentioning
confidence: 99%
“…Interestingly, the recently characterized Ins(1,4,5)P 3 kinase from the nematode Caenorhabditis elegans lacks the consensus calmodulin binding site and, not surprisingly, is insensitive to Ca 2 ϩ /calmodulin (Clandinin et al, 1998). Phosphorylation experiments demonstrated that Ins(1,4,5)P 3 kinase isoforms A and B are substrates for protein kinase C-and protein kinase A-mediated phosphorylation in vitro Wang et al, 1995;Communi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%